Eu2+ and Mn2+ co-doped Lu2Mg2Al2Si2O12 phosphors for high sensitivity and multi-mode optical pressure sensing. Issue 9 (14th April 2023) - Zheng, Zhibo; Song, Yanhua; Zheng, Baofeng; Zhao, Yanxia; Wang, Qilin; Zhang, Xiangting; Zou, Bo; Zou, Haifeng
Abstract : The Eu 2+ and Mn 2+ co-doped Lu2 Mg2 Al2 Si2 O12 phosphor has two independent high sensitivities, 1.77 and 3.53 nm GPa −1 . The decay degree of the overall integral intensity and the fluorescence intensity ratio (FIR) were put forward for pressure sensing. Abstract : Rare earth and transition metal ion doped phosphors are gradually attracting extensive attention in the field of pressure sensors. However, the lower sensitivity and single-mode pressure sensing have a significant negative impact on practical applications. In order to solve the above problems, in this work, for the first time, high sensitivity and multi-mode optical pressure sensing were achieved by co-doping Eu 2+ and Mn 2+ ions in the Lu2 Mg2 Al2 Si2 O12 (LMAS) host. The LMAS:Eu 2+, Mn 2+ phosphor has two independent high sensitivities, d λ /d P (Eu 2+ ) = 1.77 nm GPa −1 and d λ /d P (Mn 2+ ) = 3.53 nm GPa −1, related to Eu 2+ and Mn 2+ ions, respectively. In addition, the co-doping strategy proposed in this research significantly improves the pressure response range of the phosphors, and the decay degree of the overall integral intensity and the fluorescence intensity ratio (FIR) were first proposed to be used for pressure sensing. Taking what is mentioned above into account, the multi-mode optical pressure sensing can be realized with the use of the LMAS:Eu 2+, Mn 2+ phosphor.